Legal Certainty Holders of Child Rights are not Mumayyiz Post-Divorce after Their Mother Married in Indonesia - Delbi Ari Putra (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The provisions of Article 105 letter (a) of the Compilation of Islamic Law (KHI) state the mother's right to maintain a child who is not yet mumayyiz or under 12 years of age. However, the regulations do not state explicitly whether the mother's custody rights remain or transfer to another party when the mother remarries another man. This paper aims to examine the custody of children who are not yet mumayyiz after the mother re-marries in a normative juridical manner using a descriptive approach. The results of the study concluded that the mother as the holder of child custody has not been mumayyiz after her divorce, but still has the right to continue parenting rights. With note, her marriage to another man did not cause any negligence and she was still able to carry out her obligations and responsibilities to care for, nurture, and educate her. If the best interests of the child can no longer be realized and cause disputes related to child care and to obtain legal certainty, then through a court process, custody rights can be transferred to other parties which consist sequentially of the biological father, adoptive parents who get a court decision, the child's family. in a straight line upwards and adult siblings, their guardians who have received a stipulation from the court and the competent authority.